Wax transfer printing to enable robust barrier definition in devices based on non-standard porous materials. (29th March 2017) - To, Anthony; Downs, Corey; Fu, Elain
Abstract: Wax printing has become a common method of fabricating channels in cellulose-based microfluidic devices. However, a limitation of wax printing is that it is restricted to relatively thin, smooth substrates that are compatible with processing by a commercial wax printer. In the current report, we describe a simple patterning method that extends the utility of wax printers for creating hydrophobic barriers on non-standard porous substrates via a process called wax transfer printing. We demonstrate the use of multiple wax transfer cycles to create well-defined, robust, and reproducible barriers in a thick cellulose substrate that is not compatible with feeding through a wax printer. We characterize the method for (i) wax spreading within the substrate as a function of heating time, (ii) the ability to create functional barriers in a substrate, and (iii) reproducibility in line width.